Fine needle aspiration of an intranodal follicular dendritic cell sarcoma: A case report with molecular analysis and review of the literature. Issue 2 (20th August 2020) - Andersen, Michael J.; Kerr, Darcy A.; Lisovsky, Mikhail; Vaickus, Louis J.; Linos, Konstantinos
Abstract: Follicular dendritic cell sarcoma (FDCS) is a rare malignant neoplasm of follicular dendritic cell origin which can present a diagnostic challenge. Due to the rarity of this neoplasm, its molecular pathogenesis has not been fully elaborated. A previous series of 13 cases reported that 38% contained mutations of genes encoding proteins involved in negative regulation of NF‐κB. NF‐κB is a family of transcription factors regulated through multiple cellular processes known as the canonical and noncanonical pathways. Here we present the case of a 62‐year‐old man who presented with abdominal pain and systemic symptoms and was found to have a mass in the porta hepatis. Fine needle aspiration cytology demonstrated a spindle cell neoplasm with vesicular chromatin and prominent nucleoli with admixed lymphocytes. Surgical resection showed an intranodal, 7.3 × 5.5 × 3.5 cm, solid mass composed of plump, spindle to histiocytoid cells with ovoid nuclei and small, prominent nucleoli arranged in a whorled and fascicular pattern. The lesional cells stained positively for CD21, CD23, and CD35 by immunohistochemistry, consistent with a diagnosis of FDCS. Next‐generation sequencing revealed pathologic mutations in three genes involved in NF‐κB regulation pathways: NFKBIA, TNFAIP3, and TRAF3 . A pathologic TP53 mutation was also identified. This case report supports prior associations of the NF‐κB pathway dysregulation and FDCS. Additionally, it is the first reported FDCS case with TRAF3 mutation as well as the first reported case to suggest disruption in both the canonical and noncanonical NF‐κB pathways in the same lesion.